Peningkatan Kompetensi Peserta Pelatihan Jarak Jauh Teknis Keprotokolan Melalui Learning Management System (LMS) Balai Diklat Keagamaan Surabaya Tahun 2020 - Mohammad Anung Edy Nugroho (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2021)
The demands of rapid technological development in the industrial era 4.0 and also the covid-19 pandemic that happened in Indonesia encourage Education and Training Institutions to continue to move dynamically. To deal with this, Balai Diklat Keagamaan Surabaya needs to produce quality human resources through the use of optimal information technology, namely the Learning Management System (LMS). Based on these reviews, this study aims to describe how the Learning Management System (LMS) is used in Protocol Technical Distance Training and to find out how far this learning is able to improve the competence of training participants, both knowledge competence, skill competence, and attitude competence. This research was conducted on 54 participants of Protocol Technical Distance Training. The results of the study, most of the data were obtained through online media and observations, showed that there was an increase of 21.19% between the initial and final scores of knowledge competencies (from a mean of 56.07 to 77.26). From the aspect of skills, it can be seen from the completion of the assignment of participants in each training course that the scores are above completeness. From the aspect of attitude competence, it can be seen that the disciplinary aspect of the participants in participating in the training and in terms of completing tasks is always done on time. These results indicate that the use of the Learning Management System of the Surabaya Religious Education and Training Center can improve the competency of the Protocol Technical Distance Training participants.